Heart rate variability is associated with outcome in spontaneous intracerebral hemorrhage - Szabó, Jozef; Sykora, Marek (Journal of critical care, 2018)
Purpose - Autonomic imbalance as measured by heart rate variability (HRV) has been associated with poor outcome after stroke. Observations on HRV changes in intracerebral hemorrhage (ICH) are scarce. Here, we aimed to investigate HRV in ICH as compared to a control group and to explore associations with stroke severity, hemorrhage volume and outcome after ICH. - Methods - We examined the autonomic modulation using frequency domain analysis of HRV during the acute phase of the ICH and in a healthy age- and hypertension-matched control group. Hematoma volume, intraventricular extension, initial stroke severity and baseline demographic, clinical parameters as well as mortality and functional outcome were included in the analysis. - Results - 47 patients with ICH and 47 age- and hypertension matched controls were analyzed. ICH patients showed significantly lower total high frequency band (HF) and low frequency band (LF) powers (p=0.01, p<0.001), higher normalized HF power (p=0.03), and lower LF/HF ratio (p<0.001) as compared to the controls. Autonomic parameters showed associations with stroke severity (p=0.004) and intraventricular involvement (p=0.01) and predicted poor outcome independently (p=0.02). - Conclusions - Autonomic changes seems to be present in acute ICH and are associated with poor outcome independently. This may have future monitoring and therapeutic implications.